FINDING THE DRIVERS AND BARRIERS OF SUSTAINABILITY TRANSITION : An Interventionist Research in an International Contract Manufacturing Company - Kettunen, Aila (My University, 2020)
As the pressure for individual companies to take part in the sustainability transition has grown companies have hard time responding to those pressures. In this research sustainability transition of an international contract manufacturing company has been studied using the multilevel perspective framework to recognize the drivers and barriers of the transition. The research was conducted as an interventionist research, with a strong focus on the practical side of the issue, and an active participation of the researcher as a part of the target organization. First the theory of sustainability transition was discussed, and the multi-level perspective framework was introduced. Then the sustainability transition theory was brought to company level from socio-technical level by using the redefined multi-level perspective framework. The different external and internal drivers and barriers were recognized by collecting the data while working in the company. The data collection included normal day to day working and human contacts as well as different work-related documents. When the drivers and barriers were recognized they were then positioned in the framework to create clear picture of the internal and external drivers and barriers. Then the different sustainability transition pathways were studied from the company perspective and the different phases of the transition was clarified. The main managerial contribution of this study is the redefined multi-level perspective framework that can help company managers to proactively recognize the drivers and barriers of sustainability transition in their companies.

Näinä aikoina, kun paine yksityisten yritysten kestävyystransitioon on kasvanut, on myös haasteet vastata näihin paineisiin kasvaneet. Tässä tutkimuksessa tutkittiin kansainvälisen sopimusvalmistusyrityksen kestävyystransitiota multi-level perspective (MLP)-teoreettisen viitekehyksen avulla transition ajureiden ja esteiden tunnistamiseksi. Tutkimus tehtiin interventionaalisena tutkimuksena, jossa keskityttiin voimakkaasti käytännön puoleen ja tutkijan aktiiviseen osallistumiseen osana kohdeyritystä. Ensin esitettiin kestävyystransition teoria ja MLP-teoria. Sitten kestävyystransitioteoria tuotiin yritystasolle sosio-tekniseltä tasolta käyttämällä uudelleen määriteltyä MLP-viitekehystä. Eri ulkoiset ja sisäiset ajurit ja esteet tunnistettiin keräämällä tietoja työskennellessä yrityksessä. Tiedonkeruu sisälsi normaalia päivittäistä työskentelyä ja ihmiskontakteja sekä erilaisia työhön liittyviä asiakirjoja. Kun ajurit ja esteet tunnistettiin, ne sijoitettiin MLPviitekehykseen luomaan selkeä kuva sisäisistä ja ulkoisista ajureista ja esteistä. Sitten tutkittiin eri kestävyystransitioreittejä yrityksen näkökulmasta ja selvitettiin transition eri vaiheita. Tämän tutkimuksen suurin käytännön kontribuutio on uudelleen määritelty MLP-viitekehys, joka auttaa yritysjohtajia tunnistamaan ennakoivasti yrityksissään kestävyystransition ajurit ja esteet.
Keywords: Sustainability transition, Multi-level perspective, Transition pathways, Sustainable business model